PENDIDIKAN DALAM PERSPEKTIF STRUKTURAL KONFLIK - Nur Rohman (Program Studi PGMI IAI Pangeran Diponegoro Nganjuk, 2020)
Structural conflict is the antithesis of structural theory functional, where the structural theory functional very put forward the regularity in society. Perspective of conflict have a different from the functional perspective a more see a positive contribution educational institutions for the community. This perspective more emphasis on the role of power( not recognize similarities in a society). As well as in the school, education is a class variables or status.